An Alternative Approach to Labor Supply Modeling. Emphasizing Job-type as Choice Variable - John K. Dagsvik; Zhiyang Jia (Statistics Norway, Research Department, 2008)
Traditional labor supply analysis is based on the assumption that workers only have preferences over consumption and hours of work, and are able to choose consumption and hours freely within the budget constraint. Recently, various discrete choice versions of the traditional approach (with discrete hours) have become popular, but the basic assumption above is still maintained. Neither of these two approaches allows for agents'preferences over qualitative job-specific or choice restrictions facing the agents in the labor market in terms of restricted choice sets of job opportunities. In this paper we argue for an alternative modeling framework that differs from the standard models of labor supply in that the notion of job choice is fundamental. Specifically, the worker is assumed to have preferences over a latent worker-specific choice set of jobs from which he chooses his preferred job. A job is characterized with fixed (job-specific) working hours, wage rate and non-pecuniary attributes. As a result, observed hours of work and wage rate are interpreted as the job-specific (fixed) hours of work and wage rate associated with the chosen job. The discussion in this paper focuses on interpretation of different versions and extensions of the alternative framework, theoretical and practical advantages, and how this approach relates to familiar existing approaches in the literature.
Keywords: J22; C51; 330; Labor supply; non-pecuniary job attributes; non-convex budget sets; latent choice sets; random utility models.